Rapid and Efficient Extraction Method for Reverse Transcription-PCR Detection of Hepatitis A and Norwalk-Like Viruses in Shellfish - Kingsley, David H. (American Society for Microbiology, 2001)
As part of an effort to develop a broadly applicable test for Norwalk-like viruses and hepatitis A virus (HAV) in shellfish, a rapid extraction method that is suitable for use with one-step reverse transcription (RT)-PCR-based detection methods was developed. The method involves virus extraction using a pH 9.5 glycine buffer, polyethylene glycol (PEG) precipitation, Tri-reagent, and purification of viral poly(A) RNA by using magnetic poly(dT) beads. This glycine–PEG–Tri-reagent–poly(dT) method can be performed in less than 8 h on hard-shell clams (Mercenaria mercenaria) and Eastern oysters (Crassostrea virginica) and, when coupled with RT-PCR-based detection, can yield results within 24 h. Observed sensitivities for seeded shellfish extracts are as low as 0.015 PFU of HAV and 22.4 RT-PCR(50) units for Norwalk virus. Detection of HAV in live oysters experimentally exposed to contaminated seawater is also demonstrated. An adaptation of this method was used to identify HAV in imported clams (tentatively identified as Ruditapes philippinarum) implicated in an outbreak of food-borne viral illness. All of the required reagents are commercially available. This method should facilitate the implementation of RT-PCR testing of commercial shellfish.